A Priori and A Posteriori Error Estimates for Singularly Perturbed Differential and Integro-Differential Equations - Kumar, Shashikant (IIT(BHU) Varanasi, 2023)
Abstract is available in the attachment.
Keywords: Mathematical Sciences